Templatify: an e-book collection of e-cards templates / Nur Faqiha Sakina Patlillah … [et al.] - Patlillah, Nur Faqiha Sakina; Mohd Zain, Zainab; Rahim, Hainnuraqma; Mohamed, Noor Azzura; Ibrahim, Khalilah (Academy of Language Studies, 2023)
This research aim is to establish a compilation of an e-cards templates in e-book form for students and those who are interested. In line with this aim, three research objectives had been established i) to ensure everyone has access to this e-book at an affordable price. (ii) to identify student’s interest in e-book. (iii) to identify potential customers’ preferences. The data is gathered by analysing the existing templates used by university students. In addition, a pilot survey was also conducted among students in UiTM Alor Gajah, Melaka. The data were analysed using descriptive analysis. The finding reveals that majority students agree that having a template will ease their work. Therefore, there is a significant need in creating ‘e-book: Templatify’ as e-card designs that will ease the process designing their e-cards design for their future events.